Unraveling the nuclear isotope tapestry: Applications, challenges, and future horizons in a dynamic landscape - Hang Yang; Qi Feng; Weixiang Xu; Yadong Tang; Guoliang Bai; Yunli Liu; Zisen Liu; Shibin Xia; Zhenbin Wu; Yi Zhang (Eco-Environment & Health, 2024)
Nuclear isotopes, distinct atoms characterized by varying neutron counts, have profoundly influenced a myriad of sectors, spanning from medical diagnostics and therapeutic interventions to energy production and defense strategies. Their multifaceted applications have been celebrated for catalyzing revolutionary breakthroughs, yet these advancements simultaneously introduce intricate challenges that warrant thorough investigation. These challenges encompass safety protocols, potential environmental detriments, and the complex geopolitical landscape surrounding nuclear proliferation and disarmament. This comprehensive review embarks on a deep exploration of nuclear isotopes, elucidating their nuanced classifications, wide-ranging applications, intricate governing policies, and the multifaceted impacts of their unintended emissions or leaks. Furthermore, the study meticulously examines the cutting-edge remediation techniques currently employed to counteract nuclear contamination while projecting future innovations in this domain. By weaving together historical context, current applications, and forward-looking perspectives, this review offers a panoramic view of the nuclear isotope landscape. In conclusion, the significance of nuclear isotopes cannot be understated. As we stand at the crossroads of technological advancement and ethical responsibility, this review underscores the paramount importance of harnessing nuclear isotopes' potential in a manner that prioritizes safety, sustainability, and the greater good of humanity.